Fact checking in the history of uniportal video-assisted thoracoscopic surgery - Rocco, Gaetano (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
Contributing to the surgical literature with a new technique is not like patenting a new device. New techniques are meant to help our patients in the everyday practice. Conversely, new devices eventually have the same aim but marketing issues may cloud the ability to objectively verify their actual impact on patient care. In my view, a new technique is the perennial contribution a surgeon offers to the community: the very first time it is published, it doesn’t belong to you anymore—it becomes everybody’s. And everybody can perfect the technique by contributing to expanding its indications and widespread use. This is exactly the case for uniportal video-assisted thoracoscopic surgery (VATS) surgery.